SISMART: School Education Application to Create Excellent Human Resource in the Face of the Industrial Revolution Era 4.0 - Eka Kusuma Hadi Bagus Hanafi; Rina Rina; Diah Shafira Yuniar; Kendid Mahmudi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
The background is the academic environment is highly demanded to follow the development of the technology because it is intended to create superior human resources and be ready to face the industrial revolution 4.0.